Women and Torah: The Orthodox Jewish Response to Second-Wave Feminism - Shekhter, Batsheva (Iggrot Ha'Ari, 2023)
This paper explores the effects of second-wave feminism in the 1970s on the Orthodox Jewish movement within the United States. During this time, the feminist movement challenged the way women were viewed and treated in American society, leading to other denominations of Judaism soon enacting policies to reflect such change. The paper examines how this movement was received and responded to by the Orthodox Jewish leadership and seeks to explore the contradictions that arose as a result of the collision between feminism and Orthodox Judaism. Ultimately, it concludes that the feminist movement of the 1970s had a profound impact on the Orthodox Jewish movement, leading to changes in milestone events, education, and representation within the community, but also contributing to a complex and ongoing debate about the meaning and practice of Jewish tradition.